(untitled) (8gen-ART, 2023)
After The Turkish Republic founded in 1923, there have been intense studies in many fields of art, especially in painting. All the social and political developments, revolutions and social events have also affected the painters. Since the early years of the Republic, besides the subjects such as crops, harvests, threshing, tractors, peasants and farmers, Atatürk, the War of Independence and the revolutions have been among the subjects that have been extensively covered in paintings with social content. The art of painting was used as a tool in order to introduce and make the reforms popular to the public, and the artists produced works in the socialist realist direction. After the death of Atatürk in 1938, a new era began in Turkey and the Assembly elected Ismet İnönü as the President. During this period, the whole world was under the influence of the Second Word War. While new artistic formations were seen in Turkey in the 1940s, social realist painting gained meaning with the work of the Yeniler Group, which was established in 1941. The artists of the Yeniler Group, who questioned the groups before them, entered the public and produced works with social content. They approached the painting of working people and the environment they live in and observe within a social understanding of art. The works of some of the artists of the group were removed from the exhibition halls as they were seen as contrary to the national moral values. With the coming to power of the Democrat Party in 1950, the transition to the multi-party system and liberalization period began in Turkey. After this period, various trends are seen in Turkish painting art. Abstract paintings began to take the place of realistic paintings with social content in the 1940s. Although abstract painting was handled by many artists between the years 1950-1960, figurative and social-themed paintings continued to be processed with the beginning of industrialization and squatting. Some members of the Onlar Group, which was active in the early 1950s, and the artists of the Yeni Dal Group, which produced works similar to the realistic understanding of the Yeniler Group, also discussed social issues in their works during this period. In our study, the works dealing with social issues between the years of 1923 and 1960 will be examined in three parts as Atatürk Period (1923-1938), Ismet Inönü Period (1938-1950) and Democrat Party Period (1950-1960). Keywords: Turkish Painting, Social Realism, Contemporary Turkish Painting.